Project-Based Learning Strategies To Encourage Student Independence And Creativity - Nova Yunita Sari; Christi Natalia Simarmata; Eni Meliani Sipayung; Febriana Jovanka Gultom; Lesmita Munthe; Lovi Ellyta Gulo (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
21st century learning demands strategies that not only transfer knowledge, but also develop critical thinking skills, creativity, and student independence. This article aims to examine in depth the implementation of project-based learning (PjBL) strategies in encouraging student independence and creativity. This study uses a qualitative approach with a literature study method, which examines various scientific literature and relevant sources related to PjBL, learning independence, and creativity. The results of the study indicate that PjBL is able to improve student learning independence through active involvement in project planning, implementation, and evaluation. On the other hand, student creativity also develops because there is space for free, explorative, and solution-oriented thinking in solving project challenges. However, the implementation of this strategy faces challenges, such as teacher readiness, time constraints, and resource availability. Therefore, the integration of PjBL into the education system requires careful planning and support from various parties. In conclusion, PjBL is a potential strategy to create meaningful learning experiences and empower students holistically